Annual dynamics of phosphatase activities in an evergreen oak litter: influence of biotic and abiotic factors (Soil Biology and Biochemistry, 2004)
As part of a study of the processes involved in litter biodegradation, we considered the variations over 1 year of the phosphatase activities in sclerophyllous evergreen oak litter (Quercus ilex L.). Evergreen oak is representative of tree species in the forests of the French Mediterranean area. Acid (E.C. 3.1.3.2.) and alkaline (E.C. 3.1.3.1.) phosphatases, were measured over 13 months in the forest litter, along with several biotic and abiotic variables, potentially involved in the regulation of these enzymes. These comprised moisture, temperature, pH, water-extractable inorganic P (PI ), fungi, culturable heterotrophic bacteria and protein concentrations. Moisture considerably affected the production of proteins and acid phosphatases, probably formed by litter microorganisms. This result corroborated the study of Criquet et al. [Soil Biology and Biochemistry 34 (2002) 1111] which indicated that rainfall was the most important factor regulating the production and the activity of numerous enzymes in sclerophyllous forest litter. However, it appeared that moisture cannot alone predict all of the variations in phosphatase activities and the mineralisation rate of organic P (PO). Indeed, principal component analyses (PCA) and multiple regressions showed that temperature and bacterial communities were also implicated in phosphatase dynamics and PO mineralisation. Acid phosphatases were negatively correlated with the temperature, whilst alkaline phosphatases were positively correlated with this variable. The signiﬁcant correlation obtained between bacteria and PI concentrations, and the lack of correlation between bacteria and both acid and alkaline phosphomonoesterases, suggest that other important phosphatase types, such as phosphodiesterases, must be strongly implicated in PO mineralisation of the litter and in the regulation of P microbial metabolism.

Endoglucanase and β-glycosidase activities in an evergreen oak litter: annual variation and regulating factors (Soil Biology and Biochemistry, 2002)
This paper represents the third part of a larger study about the processes involved in litter biodegradation in an oak copse in France. It concerns the variations in activities of endoglucanases and of β-glycosidases over 13 months in forest litter. Evergreen oak (Quercus ilex L.) litter was taken as a model because Q. ilex is the most abundant tree species in forests of the French Mediterranean area. The activities of several endoglucanases and β-glycosidases, and the concentrations of the proteins and reducing sugars were measured in the evergreen oak litter between October 1997 and October 1998. Several biotic and abiotic factors, potentially involved in the regulation of the activities of these hydrolyzing enzymes, were also measured: culturable heterotrophic bacteria, cellulolytic bacteria and cellulolytic fungi, moisture, temperature and pH of the litter. Under this Mediterranean climate, the moisture of the litter was strongly correlated with many factors and is likely to be important in regulating the temporal dynamics of various biological parameters. A multiple regression analysis showed that the annual dynamic of the culturable heterotrophic bacteria was primarily influenced by moisture but also by variations in concentration of reducing sugars in the litter. Moreover, these bacteria were correlated with the activities of several β-glycosidases, and specifically with the N-acetyl-glucosaminidases (r=0.93). No relationships were established between the number of cellulolytic microorganisms (bacteria and fungi) and the activities of endoglucanases (i.e. cellulases and hemicellulases). The seasonal trends of certain biotic processes, and the influence of pH and of temperature on these processes are also discussed. Electrophoretic analyses were used to estimate the number of cellulase and xylanase isoenzymes in the litter, and to study their fluctuations over one year. The prevailing cellulase isoenzyme had a Rf of 0.64, and there was no relationship between the abundance of cellulolytic microorganisms and the electrophoretic profiles of the cellulases. In the case of the xylanases, the electrophoretic profiles were homogenous throughout the year, and the prevailing xylanase had a Rf of 0.75.

Biochemical and molecular characterization of a laccase from Marasmius quercophilus (APPLIED AND ENVIRONMENTAL MICROBIOLOGY, 2000)
The basidiomycete Marasmius quercophilus is commonly found during autumn on the decaying litter of the evergreen oak (Quercus ilex L.), a plant characteristic of Mediterranean forest. This white-rot fungus colonizes the leaf surface with rhizomorphs, causing a total bleaching of the leaf. In synthetic liquid media, this white-rot fungus has strong laccase activity. From a three-step chromatographic procedure, we purified a major isoform to homogeneity, The gene encodes a monomeric glycoprotein of approximately 63 kDa, with a 3.6 isoelectric point, that contains 12% carbohydrate, Spectroscopic analysis of the purified enzyme (UV/visible and electron paramagnetic resonance, atomic absorption) confirmed that it belongs to the ``blue copper oxidase{''} family. With syringaldazine as the substrate, the enzyme's pH optimum was 4.5, the optimal temperature was 75 degrees C, and the K-m was 7.1 mu M. The structural gene, lac1, was cloned and sequenced. This gene encodes a 517-amino-acid protein 99% identical to a laccase produced by PM1, an unidentified basidiomycete previously isolated from wastewater from a paper factory in Spain. This similarity may be explained by the ecological distribution of the evergreen oak in Mediterranean forest.
Keys: APS

Phenoloxidases of the white-rot fungus Marasmius quercophilus isolated from an evergreen oak litter (Quercus ilex L.) (Enzyme and Microbial Technology, 1998)
A white-rot basidiomycete, Marasmius quercophilus, was isolated from an evergreen oak litter. This fungus, which very thoroughly bleaches the whole leaf area, produces laccases, a property which has not been studied before. Except on a ground leaf medium, we did not reveal phenoloxidases other than laccases. M. quercophilus is able to transform many aromatic compounds which are by-products of lignin and tannin metabolism. We observed, for example, that lignin monomers, namely p-coumaryl, coniferyl, and sinapyl alcohols are oxidized at different rates by the extracellular crude enzyme extract. The highest production of laccases is obtained with shaking cultures on malt extract supplemented with Tween 80 (0.1%) and CuSO4 (0.5 mg l 21 ). These enzymes have an optimum activity at 80°C and a stable activity at 40°C for 18 h. The extracellular crude enzyme extract medium contains three isoenzymes with pI values of 3.8, 3.5, and 3.2. It is able to significantly reduce the kappa number (21.2%) of a kraft pulp without inclusion of any mediator